Informal caregiving and mental health: results from the Belgian health interview survey 2013 and 2018 - Filip Van Droogenbroeck; Bram Spruyt; Pierre Gérain; Laura Van den Borre; Pierre Smith; Robby De Pauw; Sarah Dury (BMC Public Health)
Abstract Background Due to a globally ageing population, the demand for informal caregivers is increasing. This study investigates the socio-demographic profile of informal caregivers in Belgium and assesses the relationship between informal care (intensity and care recipients) and mental health, considering potential moderators like education, age, and gender. Methods Using population-based data from the 2013 and 2018 waves of the Belgian Health Interview Survey (N = 14,661), we conducted multivariate (multinomial/ordinal) logistic and linear regression analyses to examine the socio-demographic profile of informal caregivers and their psychological distress, measured through the General Health Questionnaire (GHQ-12). Results The prevalence of informal caregiving increased from 10.0% in 2013 to 13.0% in 2018. Informal caregivers were predominantly female, middle-aged, and often had no paid job. High-intensity caregivers (over 20 h/week) experienced significantly higher psychological distress compared to non-caregivers, whereas lower-intensity caregivers did not. Additionally, while gender, age, and education were significant predictors of who becomes a caregiver, they did not moderate the relationship between caregiving and mental health. Conclusions Our findings suggest that the stress of caregiving is more directly related to the nature and intensity of the caregiving tasks themselves rather than the demographic characteristics of the caregivers. Interventions aimed at reducing the adverse effects of caregiving might need to be universally applicable to all caregivers, focusing on reducing the intrinsic burdens of caregiving tasks rather than targeting demographic subgroups.